SOLUSI POTRET PROBLEMATIKA MATERI MUATAN REGULASI DALAM PENANGANAN COVID-19DI INDONESIA - Ahmad Sabirin; Febrian Duta Adhiyaksa; Janna Shafira Widianti Apcar (UNES Law Review, 2022)
The COVID-19 pandemic has had a tremendous impact, ranging from the economic crisis to public health, which is the government's focus in minimizing the impact of the Covid-19 pandemic. The type of research used in this research is juridical-normative. And the purpose of this research, namely; 1) describe the regulations issued by the Central and Regional Governments in dealing with the Covid-19 Pandemic, 2) and describe solutions to overcome regulatory problems issued by the Central and Regional Governments during the Covid-19 Pandemic. The government in issuing several regulations looks inconsistent, for example; the difference in the definition of PSBB as regulated in PP No. 21 of 2020 with that regulated in the Quarantine Law. Then, regarding the Instruction of the Minister of Home Affairs Number 15 of 2021 which is considered to have neglected the regulations above. Problems with existing regulations, the government needs to break the chain of spread of the Covid-19 pandemic with the product of regulations based on the Tiered Law Theory by Hans Nawiasky. This theory then when associated with problems in Indonesia can make Article 34 paragraph (3) of the 1945 Constitution and Law no. 6 concerning Health Quarantine is a reference for the government in formulating the rules under it, in matters relating to regulations during the Covid-19 pandemic so that it becomes a solution in overcoming the regulatory problems of handling the Covid-19 pandemic.